Factors associated with the early discontinuation of intra uterine device : A nested case control study. - Thapa, Subash (2011)
ABSTRACT: Discontinuation of any contraception method is of greater interest because it leaves women unprotected from the risk of unwanted pregnancy. A nested case control study was conducted to identify the factors associated with the early discontinuation of IUCD. A group of women, inserting IUCD from 14th April 2003 to 12th April 2004 at the Kchetrapati Family Welfare Centre, Kathmandu were taken as study cohort. Result show that the mean duration of IUCD use for both continuers and discontinuers was found 54 months. The early discontinuation is almost 40.5% among the total respondents. Among the total discontinuers, discontinue within first year of use is very high. Side effects and health concern has been seen as the major reason for IUCD discontinuation. Reproductive intention, experience of side effects and follow up practice were associated with early discontinuation of IUCD. Place of residence and sex preference were also associated with the discontinuation behavior. This IUCD discontinuation study, along with future research in this area, can help policymakers and program managers track family planning progress and foster them to meet the goal of reproductive health for all.